DNA labelling in live cells via visible light-induced [2+2] photocycloaddition. Issue 27 (15th March 2023) - Michenfelder, Rita T.; Delafresnaye, Laura; Truong, Vinh X.; Barner-Kowollik, Christopher; Wagenknecht, Hans-Achim
Abstract : Styrylquinoxaline (SQ)-modified DNA is labelled with SQ-modified dyes in live HeLa cells via [2+2] photocycloaddition using visible light irradiation. Abstract : We introduce a visible light-driven ( λ max = 451 nm) photo-chemical strategy for labelling of DNA in living HeLa cells via the [2+2] cycloaddition of a styrylquinoxaline moiety, which we incorporate into both the DNA and the fluorescent label. Our methodology offers advanced opportunities for the mild remote labelling of DNA in water while avoiding UV light activation.